Askeri ceza hukukunda firar suçları - Şimşek, Mustafa (My University, 2004)
1982 Anayasası'nın 72. maddesine göre, askeri hizmet bir vatan hizmeti olarak her Türkün hakkı ve ödevidir. Bu hizmetin Silahlı Kuvvetlerde veya diğer kamu hizmeti alanlarında ne şekilde yerine getirileceği veya getirilmiş sayılacağı kanunla düzenlenecektir. Ordunun en temel prensibi, askeri hizmetin ifası amacıyla askeri sadakat ile hazır bulunmak ve emirlere itaat etmektir. Askeri hizmetin ihlalini teşkil eden suçlardan biri de firar suçudur. Suçun en temel özelliği ise sadece asker kişiler tarafından işlenebilen mahsus suçlardan veya başka bir deyişle sırf askeri suçlardan olmasıdır. Kanunkoyucu tarafından ertelenmesi mümkün olmayan, başka bir tedbir veya cezaya çevrilemeyen suçlardan kabul edilmesi ile zamanaşımı bakımından farklı hükümler öngörülmesi, suçun askeri hizmeti ve askeri disiplini ne kadar ağır ihlal ettiğinin ifadesidir. Askeri hizmetten kaçmak Silahlı Kuvvetlere sahip her ülkenin mevzuatında suç olarak öngörülen bir fiildir. Firar suçu, Mukayeseli hukukta askeri ceza kanununda veya (askeri ceza kanununa sahip olmayan ülkelerde ise) genel ceza kanununun ayrı bir faslında yer alan bir askeri suçtur. Tez çalışmamızda firar suçlarının hukuki özellikleri, suçun unsurları, suçu etkileyen haller, yaptırım ile kovuşturma usulü hususları incelenerek askeri ceza hukukumuzdaki yeri ve önemi açıklanmaya çalışılmıştır. Firar suçunun diğer askeri hizmetten kaçma fiilleri ile mukayesesi yapılarak suçun ayırt edici yönleri ifade edilmiştir.

According to the 72nd article of the 1982 Constitution, doing military service is the right and duty for each Turk in order to service his country. How this service is performed or considered as completed in the military or public services is regulated by way of law. It is mandatory that every eligible Turk do military service. The main principle of the army in order to perform military service is to obey the orders and to be ready for mission with loyalty. One of the ways to break this law is to desert. Military desertion is accepted as a crime in almost every nation which owns military forces. The main characteristics of this crime is only military personel can commit this; that is to say, it is a military crime. That the crime of desertion cannot be postponed and cannot be converted to other measures or penalties by the lawmaker and that even from the aspect of expiration various decisions are given accordingly are all the expressions showing how seriously it affects the military service and discipline. Desertion is accepted as a crime in the laws of every country which possesses armed forces. In countries having a military penal law or having a civilian law instead, it is considered in the comparative law as a common military crime owing to this property. In the thesis, the position and significance of the crime of desertion in our military penal law is explained saerching its qualities, structure, affecting factors and cases and the ways of sanction and investigation. By comparing desertion with other similar crimes of running away from military service, the descriminating characteristics of the crime are expressed. To sum up, the crimes of military desertion, together with all qualities and discipline, and the approperiation to the national defense are searced considering in each society that owns an army throughout history.
Keywords: Askeri Hukuk